Barriers and facilitators to disclosure of sexual violence and relationship with symptoms of depression, anxiety and stress - Eva Bryndís Pálsdóttir 1982- (2020)
. Objective. Disclosing sexual violence can be a hard process for survivors; most receive both positive and negative responses. Survivors are encouraged to talk about the experience and disclosure is associated with positive outcomes. The current study used thematic analysis to identify what facilitators and barriers survivors of sexual violence in Iceland experience and their relations with psychological symptoms. Method. Study on trauma and mental health in the Icelandic population conducted by Reykjavik University. The participants were a random sample from the National Registry of Iceland. The sample consisted of 747 respondents, while participation involved answering questionnaires and open-ended questions in a telephone survey. The data were collected by trained undergraduate psychology students and part-time callers receiving payment. The data collectors followed an exact script and recorded answers using data entry software. Results. The analysis revealed four overarching themes and sixteen subthemes. The overarching themes were: personal barriers, external barriers, personal facilitators and external facilitators to disclosure of sexual violence. The results showed that women are more likely than men to experience facilitators to disclosure and children are more likely than adults to delay disclosure of sexual violence. There was not a significant difference in the scores for depression, anxiety or stress when compared to personal or external barriers to disclosure. Conclusion. More survivors experienced facilitators than barriers to disclosure of sexual violence. Very few survivors experienced external barriers compared to personal barriers. Both personal facilitators and external facilitators seemed to play an equally important part in disclosure. .